Profil Asam Lemak kuning Telur Puyuh Jepang yang Disuplementasi Jus Daun Afrika (Vernonia amygdalina Del) dalam Air Minum: Fatty Acid Profile of Japanese Quail Egg Yolk Supplemented with African Leaf Juice (Vernonia amygdalina) in Drinking Water - dwi margi suci; Widya Hermana; Dudung Abdul Malik; Innaka Hasbullah (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2023)
This study aimed to determine the effect of african leaf juice (Vernonia amygdalina) supplementation in drinking water on the performance and fatty acid profile of quail egg yolk. A total of 120 eight-week-old Japanese quail was used in this study and reared for 6 weeks in colony cage. Completely randomized design with three treatments and five replications were used in this study. The treatments were control treatment (without african leaf juice supplementation), 3 ml bird-1 day-1 supplementation and 6 ml bird-1 day-1 supplementation. The data were analyzed for variance, the significant difference results were tested by LSD test at p<0.05. The variables were feed consumption, drinking water consumption, egg production, egg weight, egg mass, feed conversion and mortality as well as analysis of egg yolk fatty acid. The results showed that african leaf juice contained high flavonoid and saponin. Daily supplementation of african leaf juice in drinking water at the doses 3 and 6 ml bird-1 day-1 did not affect the performance of laying quails. Mortality in treated quail was 33.3% and this value was lower than control. Ratio of omega 6 and omega 3 was ranging 24.5% – 26.2% fat. It could be concluded that african leaf juice could use to reduced mortality. Key words: african leaf, fatty acid profile, quail performance, Vernonia amygdalina